Sustainable Strategies in Sports Mega-Events: An Analysis of Soccer World Cups - Caio Henrique Quemel Siqueira; Alexandre Lima de Araújo Ribeiro (Universidade Salgado de Oliveira, 2021)
The present study aimed to analyze the sustainable strategies in the areas of energy and garbage and waste management adopted by the host countries of the FIFA World Cups in 2006 (Germany), 2010 (South Africa), and 2014 (Brazil). Therefore, in addition to a documentary analysis of the sustainability projects (also known as Green Goal), a search was performed for scientific studies that approached the topic of sustainable development/sustainability in mega sporting events. To perform the searches at Scholar Google and Scielo, the keywords "sustentabilidade", "Copa do Mundo", "Copa do Mundo de Futebol", "Green Goal" "sustainability", e "FIFA World Cup" was used. As a result, it was found that each host country had at least two measures in common with the others for the management of waste, with a difference only in the form of application. Also, an important common project for all countries was the use of recyclable cups, which incidentally, was the main measure adopted by Germany during the 2006 FIFA World Cup, and repeated in the subsequent cups. The other measures adopted by each host country, despite having similarities, differed in plan and execution.